Clinical Aspects of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis With Severe Ocular Complications in Taiwan - Ma, David Hui-Kang; Tsai, Tsung-Ying; Pan, Li-Yen; Chen, Shin-Yi; Hsiao, Ching-Hsi; Yeh, Lung-Kun; Tan, Hsin-Yuan; Lu, Chun-Wei; Chen, Chun-Bing; Chung, Wen-Hung (Frontiers in Medicine, 2021)
Over the last decade, there has been tremendous progress in both the understanding and treatment of SJS and TEN. To understand whether this has resulted in better ophthalmic outcomes, we aimed to study the incidence of SOCs among SJS/TEN patients, major causative medications, and the final outcome of affected patients. Using electronic medical records review of patients of Chang Gung Memorial Hospital Linkou Branch from 2010 to 2020 , 119 patients (236 eyes) received ophthalmic consultation during the acute stage and were recruited in this study. Sotozono’s grading score systems for acute and chronic SJS/TEN were employed for comparison. There were 46 male and 73 female patients with a mean age of 45.6 +/- 22.7 years old (2- 90 years). The numbers of patients with SJS, overlap syndrome, and TEN were 87, 9, and 23, respectively. In total, 55 patients had SOCs, which comprised 46.2% of patients who underwent ophthalmic examination and 18.7% of the total patients (n=294). Allopurinol is the most common culprit drug causing SOCs followed by oxcarbazepine and carbamazepine. Hyperemia was the most common chronic stage ocular complication (51.69%) followed by dry eye (49.2%), SPK (49.58%), meibomian gland dysfunction (38.14%), and mucocutaneous junction involvement (26.27%). The correlation between Stozono's acute staging (pregrade) and chronic score showed a positive relationship (Pearson's correlation coefficient (r) = 0.48, p<0.001). This finding implies that acute manifestation is a good indicator for chronic sequelae. Finally, the average chronic grading scores in patients receiving systemic corticosteroid combined with etanercept treatment were significantly lower than those in the corticosteroid only group, suggesting the potential therapeutic benefit of etanercept treatment.